2016
DOI: 10.1111/cdev.12693
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Children's Corepresentation of Self and Other in Joint Action

Abstract: Previous research has shown that children aged 4-5 years, but not 2-3 years, show adult-like interference from a partner when performing a joint task (Milward, Kita, & Apperly, 2014). This raises questions about the cognitive skills involved in the development of such "corepresentation (CR)" of a partner (Sebanz, Knoblich, & Prinz, 2003). Here, individual differences data from one hundred and thirteen 4- to 5-year-olds showed theory of mind (ToM) and inhibitory control (IC) as predictors of ability to avoid CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 71 publications
1
15
0
Order By: Relevance
“…This suggests that human subjects not only represent their own task and actions, but also their partner's, which is supported by neuroimaging studies (Wen & Hsieh, 2015). This Joint Simon effect appears rather late in human ontogeny and has been linked to Theory of Mind development (Milward, Kita, & Apperly, 2016). Recently, a joint Simon effect and thus action co-representation has been demonstrated in common marmosets (Miss & Burkart, in press).…”
Section: ) Callitrichid Communication and The Mirror System Hypothesismentioning
confidence: 73%
“…This suggests that human subjects not only represent their own task and actions, but also their partner's, which is supported by neuroimaging studies (Wen & Hsieh, 2015). This Joint Simon effect appears rather late in human ontogeny and has been linked to Theory of Mind development (Milward, Kita, & Apperly, 2016). Recently, a joint Simon effect and thus action co-representation has been demonstrated in common marmosets (Miss & Burkart, in press).…”
Section: ) Callitrichid Communication and The Mirror System Hypothesismentioning
confidence: 73%
“…The current study alone cannot distinguish between children representing only their own part and an individual goal in the Joint Action condition versus representing their own part and goal, but also their partner’s. Existing evidence that children from at least 4 years old do co-represent a partner’s task apparently automatically [ 12 , 13 , 14 ] and that they show increased motor system activation when actively engaged in the task than when observing [ 18 ] point towards the latter argument, but this should be investigated further.…”
Section: Discussionmentioning
confidence: 99%
“…Developmental work has shown interference effects in children [ 12 , 13 ] and has highlighted the role of Theory of Mind in keeping self and other apart. Milward, Kita & Apperly [ 14 ] found that children who were better at avoiding interference from a co-actor’s task were also better on a battery of Theory of Mind tasks. The authors argue that this is because children who are better at Theory of Mind are better able to keep representations of self and other separate.…”
Section: Introductionmentioning
confidence: 99%
“…A less “mentalistic” interpretation could be proposed ( D’Entremont and Seamans, 2007 ), but these results nevertheless highlight children’s motivation for reinstating joint action toward a shared goal. The development of this capacity has received much attention from researchers, as the initiation of joint attention appears to be strongly related to language comprehension and production in the second and third year of life ( Colonnesi et al, 2010 ; Cochet and Byrne, 2016 ), as well as to theory of mind ability (e.g., Charman et al, 2000 ; Milward et al, 2017 ) in both typical and atypical development (e.g., Adamson et al, 2017 ).…”
Section: How Does Communication Develop In the Context Of Social Playmentioning
confidence: 99%